Resources for forensic psychology - Sexton, Ellen A (2004)
Libraries supporting a forensic psychology undergraduate and/or graduate level college program need to collect materials from a range of disciplines – psychology, law, psychiatry and criminal justice. In this guide I identify the major reference works, journals, databases and other resources that should be in a good forensic psychology collection